Copper deficiency-associated myelopathy in cryptogenic hyperzincemia: a case report - Mutti, Carlotta; Bazzurri, Veronica; Tsantes, Elena; Curti, Erica; Parrino, Liborio; Granella, Franco (Acta Biomedica Atenei Parmensis, 2021)
Copper deficiency syndrome is an underestimated cause of posterior myelitis. We describe the case of a 41-year-old woman, who developed a subacute ataxic paraparesis associated with low back pain. Her 3T spine MRI showed a thin hyperintense FS-Echo T2 longitudinally extensive lesion involving the posterior columns of the cervical cord (from C2 to C6). An extensive diagnostic work-up excluded other causes of myelopathy and blood tests pointed out hypocupremia and mild hyperzincemia. Patients affected by this rare form of oligoelement deficiency typically develop progressive posterior column dysfunction with sensory ataxia and spasticity, sometimes associated with sensori-motor polyneuropathy. Clinical and radiological characteristics of posterior myelopathy due to copper deficiency are briefly reviewed. Physicians should be aware of this condition since a prompt introduction of copper supplementation can avoid progression of the neurological damage.